Ekonomi Kreatif Di M-Bloc Space Jakarta Sebagai Kegiatan Wisata - Salsabilla Putri Chairunissa; Gde Indra Bhaskara (JURNAL DESTINASI PARIWISATA, 2022)
The term of creative economy is developed from the concept of creativity-based capital which hasthe potential to increase economic growth in a region. Creativity is considered having capability indriving business opportunities for small businesses through the development of souvenirs, folkfestivals, and so on. Creative economy and the tourism sector are two things that influence andsynergize with each other if managed properly. This study uses a qualitative method which aims toidentify tourism in M-Bloc Space Jakarta through the creative economy. The type of data used isqualitative data with data collections carried out through observation, in-depth interviews, anddocumentaries. The data analysis used is descriptive qualitative analysis. The results of this studyindicate that the creative economy at M-Bloc Space Jakarta consists of eight creative economy subsectors,namely advertising, art market, crafts, design, fashion, music, publishing and printing, andculinary. Creative Economy at M-Bloc Space Jakarta as a tourism activity consists of (3S) Something todo, Something to see, Something to buy.Keyword: ekonomi kreatif, kegiatan wisata, creative hub, m-bloc space Jakarta.